Comparison of linoleic acid-containing water-in-oil emulsion with urea-containing water-in-oil emulsion in the treatment of atopic dermatitis: a randomized clinical trial - Nasrohalli SA; Ayatollahi A; Yazdanparast T; Samadi A; Hosseini H; Shamsipour M; Akhlaghi AA; Yadangi S; Abels C; Firooz A (Dove Medical Press, 2018)
Saman Ahmad Nasrollahi,1 Azin Ayatollahi,1 Taraneh Yazdanparast,1,2 Aniseh Samadi,1 Hamed Hosseini,3 Mansour Shamsipour,4 Ali Asghar Akhlaghi,5 Somayeh Yadangi,1 Christoph Abels,6 Alireza Firooz1,2 1Center for Research and Training in Skin Diseases and Leprosy, 2Telemedicine Research Center, National Research Institute of Tuberculosis and Lung Diseases (NRITLD), Shahid Beheshti University of Medical Sciences, 3Clinical Trial Center, 4Department of Research Methodology and Data Analysis, Institute for Environmental Research, Tehran University of Medical Sciences, 5Department of Epidemiology and Reproductive Health, Reproductive Epidemiology Research Center, Royan Institute for Reproductive Biomedicine, ACECR, Tehran, Iran; 6Dr. August Wolff GmbH & Co. KG Arzneimittel, Bielefeld, Germany Background: Application of topical moisturizers is an essential part of the management of atopic dermatitis (AD). Linoleic acid (LA), the most abundant fatty acid in the epidermis, and its derivatives have an essential role in the structure and function of the epidermal barrier, and their defects are prominent in AD. The aim of this study was to compare the efficacy and safety of two cosmetic products containing either LA or urea in patients with AD.Patients and methods: A total of 20 patients with AD who met the eligibility criteria and provided written informed consents were enrolled in this randomized, intra-individual split-body, single-center trial. Symmetrical lesions of patients were randomized for treatment with LA- or urea-containing water-in-oil (w/o) emulsions applied two to three times daily for 4 weeks. The efficacy of the two products was evaluated by local Scoring Atopic Dermatitis (SCORAD) of both lesions and also patient (or guardian) satisfaction. In addition, trans-epidermal water loss (TEWL), stratum corneum (SC) hydration, pH, sebum, temperature, erythema, melanin content, and ultrasonographic thickness and echo density of epidermis and dermis were measured before, and 2 and 4 weeks after, treatment. Results: Four weeks of treatment with the LA-containing product resulted in a significant decrease in local SCORAD, TEWL, erythema, and echo density of dermis, as well as an increase in SC hydration compared to baseline. The urea-containing product also reduced the local SCORAD and echo density of dermis and increased SC hydration. In contrast to the LA-containing product, changes in TEWL and erythema were not significant. Moreover, the reduction of erythema was significantly higher in the LA-containing product-treated side compared to the urea-containing product-treated side (p = 0.006). Conclusion: Both LA- or urea-containing w/o emulsions can significantly improve barrier dysfunction and clinical severity of AD. In agreement with literature, it was confirmed that an LA-containing w/o emulsion exhibited erythema-reducing effects. Since emollients should be used on a regular basis, patients should choose a product by individual preference following recommendation by their dermatologists. Keywords: emollient, moisturizer, humectants, epidermal barrier, erythema